EVALUASI APLIKASI SMS GATEWAY BERBASIS WEB PADA AMIK AKMI BATURAJA MENGGUNAKAN METODE USABILITY TESTING - Muhajir Arafat; Yunita Trimarsiah (Jurnal Ilmiah Matrik, 2017)
Baturaja is an educational institution that implements a web based SMS Gateway Application. The application is used to promote, inform the admission of new students of AKMI Baturaja campus. The application can send messages to prospective new students whose phone numbers are obtained from various schools visited by new admissions committee. The application provides the ease of providing information, messages related to promotion and information about AKMI Baturaja simultaneously with fast timing so that the PMB does not experience difficulties in sending messages one by one to all new student candidate phone numbers. This evaluation is conducted to analyze whether the application has acceptability based on usability criteria to measure correlation level between Learnability, efficiency, memorability, error, and statisfaction. This research was conducted by giving questionnaires to 50 Respondents. The results of this study is expected to be an input for the development of these applications in the future.